Respuestas

2013-09-23T01:38:55+02:00
Como se trata de operaciones con suma y resta, porsupuesto que se cumple la propiedad asociativa; veamos:
A)   (-4) + (-2) + (+5)
          
       
  [(-4) + (-2)] + (+5)=                        (-4) + [(-2) + (+5)]=
           [-4-2] + 5=                                   -4 + [-2 + 5 ]=
            [-6] + 5=                                       -4 + [3]=
                 -1                                                 -1

B)   (-2) + (+5) + (-3)
                               [(-2) + (+5)] + (-3)=                  (-2) + [(+5) + (-3)]=
                                [-2 + 5] -3=                              -2 +  [5 - 3]=
                                  [3] -3=                                     -2 + [2]=
                                     0                                               0